Nine letters from Patriarch German Andjelic - Spasović, Ivana (Napredak, 2021)
The Archive of the Serbian Academy of Sciences and Arts is the home of the Legacy of Patriarch German Andjelic, who headed the Karlovac Archbishopric from 1879 to 1888. A particularly important part of the collection are his letters. Out of the Patriarch’s copious correspondence, nine letters were selected for their exposition of the Patriarch’s views on important issues in the late 19th century. These letters describe the temptations of the times in which Patriarch German Andjelic lived but also give a portrait of his character and especially his gift for diplomacy. This paper also presents important events in his biography.
Keywords: Patriarch German Andjelic; Austria-Hungary; Bosnia and Herzegovina; Karlovac Archbishopric